Strategi Peningkatan Produktivitas Industri Kreatif Handycraft Upaya Pengelolaan Sumber Daya Berbasis Masyarakat - Ign Sri Seventi P; Mahastuti Agung; - Rahmawati; Sarah Rum Handayani; Anastasia Riani S (Conference In Business, Accounting, And Management (CBAM), 2012)
Research and development aims to examine and develop models of training and teaching materials (modules) that are required in the effort of improving the performance of their businesses. Training needs analysis conducted with the concept entrepreneurship small business, namely the implementation of management functions in the production, marketing, finance, management organizations and entrepreneurial spirit of qualified small business. Training needs to develop a spirit of entrepreneurship is 80% with the need include: leadership, self-motivation to become a man of learning and results orientation in the business. Training needs for production handycraft activities is 100% with the need include the administrative aspects of the production, quality control and production of knowledge about workplace safety and health. Potential training needs to develop a financial management business amounted to 83% with aspect needs include financial plan preparation, practical healthy separation of personal paternity and business bookkeeping and practical for small business. Potential training needs for marketing is 73%. Themodul are been developed in this research are entrepreneurship, handycraft bag from batik, and accounting.Keywords: entrepreneurship, management organization, marketing, production, and finance (accounting)